Weapon detection with FMR-CNN and YOLOv8 for enhanced crime prevention and security - Shanthi P; Manjula V (Scientific Reports)
Abstract In modern days, increasing weapon-related threats in public places have created an immediate need for intelligent surveillance systems to detect crime in real-time. Traditional surveillance systems have struggles with recognizing small objects, occlusion, and the time it takes to respond, which makes them ineffective in crowded and fast-changing situations. To overcome these challenges, the suggested system combines closed-circuit television (CCTV) surveillance cameras with advanced deep learning methods, image processing, and computer vision techniques for real-time crime prediction and prevention. This study proposes a hybrid deep learning framework that merges a Faster region convolutional neural network and Mask Region Convolutional Neural Network, named FMR-CNN. The novel approach FMR-CNN represents a significant advancement towards improving object recognition and segmentation of images and videos. It has been combined with YOLOv8 to increase the real-time detection speed and localization accuracy significantly. Such a combination enables the concurrent utilization of high-resolution spatial context information and rapid frame-wise predictions, thus making it well-suited for continuous video surveillance tasks. The model was trained and tested on a five labeled class annotated dataset, where MobileNetV3 features are extracted to simulate real-world surveillance conditions. Experimental results show the hybrid model attains detection accuracy of 98.7%, average precision (AP) of 90.1, and speed of 9.2 frames per second (FPS), and generalizes to varied lighting, occlusion, object scales, and reduced computational complexity, making it highly effective for crime prevention. Using these models benefits police departments and law enforcement agencies, as it allows them to detect criminal offenses earlier and avoid untoward situations.